The Influence of Subgrade CBR Value and Concrete Quality on Rigid Pavement Thickness (Case Study: Desa Simpang/Berbak to Simpang Ma. Sabak Road) - Noka, Hardiani Nofriza Zarisma; Nurdin, Ade; Abiyoga, Nurza Purwa (Universitas Ibn Khaldun, 2025)
Roads are the primary infrastructure for land transportation, facilitating traffic from one place to another. The road from Desa Simpang/Berbak to Simpang Ma. Sabak in Muara Sabak Timur District, Tanjung Jabung Timur Regency, faces a significant issue with low California Bearing Ratio (CBR) values of the subgrade soil. These low CBR values can lead to instability and deformation of the subgrade, ultimately damaging the rigid pavement built upon it. This study aims to evaluate the influence of subgrade CBR values and concrete quality on the thickness of rigid pavement for the road from Desa Simpang/Berbak to Simpang Ma. Sabak. The research employs a quantitative approach using the AASHTO 1993 method. The results indicate that subgrade CBR values and concrete quality significantly affect the thickness of rigid pavement. Higher CBR values allow for a reduction in concrete slab thickness, while higher concrete quality increases the modulus of elasticity and flexural strength of the concrete, enabling a reduction in slab thickness. However, the influence of CBR values is more significant than that of concrete quality, particularly at higher concrete grades.In conclusion, improving subgrade CBR values is more effective in reducing rigid pavement thickness than solely enhancing concrete quality. Further economic analysis is recommended to evaluate the most cost-effective combination of concrete quality and subgrade CBR values, considering both construction and long-term maintenance costs.